Delivery of A Chemically Modified Noncoding RNA Domain Improves Dystrophic Myotube Function - Zeinabou Niasse‐Sy; Bo Zhao; Ajda Lenardič; Huyen Thuc Tran Luong; Ori Bar‐Nur; Johan Auwerx; Martin Wohlwend (Advanced Science)
Abstract Fast twitch muscle fibers are prone to degradation in skeletal muscle pathologies, such as sarcopenia and muscular dystrophies. We previously showed that the exercise‐induced long noncoding RNA CYTOR promotes fast‐twitch myogenesis. Here, we identify an independent functional element within human CYTOR, and optimize its RNA delivery. In human primary myoblasts exogenous CYTOR exon 2 recapitulates the effect of full‐length CYTOR by boosting fast‐twitch myogenic differentiation. Furthermore, chemically modified CYTOR exon 2 RNAΨU (N1‐me‐PseudoU, 7‐methyl guanosine 5′Cap, polyA) enhances RNA stability and reduces immunogenicity to CYTORexon2 RNA. Viral‐ or chemically optimized RNA‐mediated CYTORexon2 administration drives commitment toward myogenic maturation in Duchenne muscular dystrophy‐derived primary myoblasts, myogenic progenitor cells, and mouse embryonic stem cells. Furthermore, CYTORexon2, m1ΨU improves key disease characteristics in dystrophic myotubes, including calcium handling and mitochondrial bioenergetics. In summary, we identify CYTOR exon 2 as the functional domain of CYTOR that can be delivered in a disease context using chemical modifications. This is of particular importance given the susceptibility of fast muscle fibers in different muscle pathologies such as aging and dystrophies, and the oncogenic effect of CYTOR exon 1. This study, therefore, highlights the potential of identifying functional domains in noncoding RNAs. Delivery, or targeting of RNA domains might constitute next‐generation RNA therapeutics.